2011
DOI: 10.1086/661104
|View full text |Cite
|
Sign up to set email alerts
|

A Head-to-Head Comparison of Hydrogen Peroxide Vapor and Aerosol Room Decontamination Systems

Abstract: One HPV generator was more effective than 2 aHP machines for the inactivation of G. stearothermophilus BIs, and cycle times were faster for the HPV system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 28 publications
3
75
0
Order By: Relevance
“…11,62 One manufacturer (ASP Glosair) states a particle size of 8e10 mm whereas another manufacturer (Oxypharm Nocospray) states a smaller particle size of 0.5 mm. 63,69,70 The dose typically recommended for hospital rooms is 6 mL/m 3 , although multiple cycles of this dose have been used in several studies. 69,71 Following exposure, the aerosol is left to decompose naturally without any active aeration system.…”
Section: Limitations Of Conventional Cleaning and Disinfectionmentioning
confidence: 99%
“…11,62 One manufacturer (ASP Glosair) states a particle size of 8e10 mm whereas another manufacturer (Oxypharm Nocospray) states a smaller particle size of 0.5 mm. 63,69,70 The dose typically recommended for hospital rooms is 6 mL/m 3 , although multiple cycles of this dose have been used in several studies. 69,71 Following exposure, the aerosol is left to decompose naturally without any active aeration system.…”
Section: Limitations Of Conventional Cleaning and Disinfectionmentioning
confidence: 99%
“…A 6-log kill is definitely appropriate for terminal sterilization of critical medical devices if the devices are used in normally sterile body sites. 2 The goal of room decontamination is significantly different: to eliminate potentially pathogenic microorganisms contaminating room surfaces.…”
Section: Hydrogen Peroxide Vapor and Aerosol Room Decontamination Sysmentioning
confidence: 99%
“…9 Finally, our study showed incomplete distribution from one of the systems. 10 This means that some areas of a hospital room get a lower dose of hydrogen peroxide than do other areas, which could contribute to the fact that log reductions achieved in vitro are not realized in all parts of the room. There is perhaps a parallel with liquid cleaning and disinfectants, in which more than a 2-log reduction in vitro does not eradicate pathogens because of limitations in achieving adequate distribution and contact time.…”
Section: Robertsmentioning
confidence: 99%
“…These comprise either stamped metal discs or papers onto which spore suspensions of either Bacillus subtilis, or more commonly Geobacillus stearothermophilus, have been deposited. A number of studies on the efficacy of HPV generators have been conducted using commercial BIs, e.g., Fu et al (2012) and Holmdahl et al (2011). Moreover, published studies routinely fail to provide details of the spatial and temporal HPV concentrations achieved during decontamination.…”
Section: Introductionmentioning
confidence: 99%